Faktor-Faktor Yang Berhubungan Dengan Perkembangan Produk Tabungan Haji Perbankan Syariah Di Indonesia - aqwa daulay (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2017)
Development of the market share in Islamic banking products become a benchmark for the development of an Islamic banking, then one of the products that encourage increased funding product is a savings product Hajj. Therefore, this paper aims to provide information and describing any factors associated with the development of Islamic banking products hajj savings. The findings in this study, there are three factors associated with the development of hajj savings products are; 1) factors relating directly to the products, such as; contract and services used, 2) government policy regarding Hajj quota limitation that requires waiting list mechanism, 3) the increase in revenues Muslim community.